2008
DOI: 10.1016/j.physletb.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of statistical multifragmentation model simulations with canonical thermodynamic model results: A few representative cases

Abstract: The statistical multifragmentation model (SMM) has been widely used to explain experimental data of intermediate energy heavy ion collisions. A later entrant in the field is the canonical thermodynamic model (CTM) which is also being used to fit experimental data. The basic physics of both the models is the same, namely that fragments are produced according to their statistical weights in the available phase space. However, they are based on different statistical ensembles, and the methods of calculation are d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…These are not available to us. However for the only cases investigated we found that CTM and SMM results were quite close [21] so the correspondence we have found here between transport model results and CTM will presumably hold for SMM also. Multiplicity distributions in 16 O+ 80 Br were done with dynamic models before.…”
Section: Resultssupporting
confidence: 73%
“…These are not available to us. However for the only cases investigated we found that CTM and SMM results were quite close [21] so the correspondence we have found here between transport model results and CTM will presumably hold for SMM also. Multiplicity distributions in 16 O+ 80 Br were done with dynamic models before.…”
Section: Resultssupporting
confidence: 73%
“…The nuclear breakup of Au nuclei depending on the excitation energy E * was simulated using the Monte Carlo generator GEMINI++ [1285] and SMM [1286]. The MC simulation showed that whenever the nucleus breaks up there will be at least one neutron emitted.…”
Section: A Dedicated Eic Detectormentioning
confidence: 99%
“…SMM is more general but requires complicated Monte Carlo simulations. In typical physical situations the two models give very similar results [3].…”
Section: Introductionmentioning
confidence: 82%